THE IMPLEMENTATION OF THE INTERCULTURAL APPROACH IN THE ENGLISH COMMUNICATION FOR MANAGEMENT PURPOSES - DIALLO, Samou Lamine (My University, 2020)
Nowadays, it is almost impossible for a manager to have an international mobility without having any intercultural competence due to the large presence of world globalization. The world globalization requires a great sense of awareness linguistically with the English language but also in terms of interculturality. The purpose of this study is then to show the importance that the intercultural approach plays in English for specific purposes particularly in management in terms of communication, considering English language as an international language, and language of Globalization. Another purpose of this study is to track whether the intercultural approach course is taken into consideration in management institutes English Program and if the time and the way is appropriate or not. The data gathered was obtained by the use of research instruments like learners and teachers’ questionnaire, also with the classroom observation of the “High International Management Institute” located in Oran. The findings of this investigation show off that the intercultural approach course is not taken into consideration as it should be; and that the time available for the English class is not enough to make learners more aware about it. Finally, this study aims at proposing some suggestions to compensate those lacks in terms of intercultural approach course implementation in English program for managers.
Keywords: English for Specific Purposes; English for Management; Intercultural Approach; World Globalization; Intercultural Awareness